A Scalable, One-Pot Synthesis of 1,2,3,4,5-Pentacarbomethoxycyclopentadiene - Radtke, M. Alex; Dudley, Caroline C.; O’Leary, Jacob M.; Lambert, Tristan H. (Synthesis, 2019)
1,2,3,4,5-Pentacarbomethoxycyclopentadiene (PCCP) is a strong organic acid and a precursor to useful organocatalysts, including chiral Brønsted acids and silicon-based Lewis acids. The synthetic route to PCCP, first reported in 1942, is inconvenient for a number of reasons. The two-step synthesis requires the purification of intermediates from intractable side-products, high reaction temperatures, and extensive labor (3 days). We have developed an improved procedure that delivers PCCP efficiently in 24 hours in one pot at ambient temperature and without isolation.
Keywords: Brønsted acid; PCCP; cyclopentadiene; dimethyl malonate; dimethyl acetylenedicarboxylate